Direct numerical simulations of particle sedimentation with heat transfer using the Lattice Boltzmann method - Yang, Bo; Chen, Sheng; Liu, Kai (Elsevier, 2017)
In most realistic gas–solid flow, the difference of particles’ temperature is significant. The heat transfer induced by temperature difference between particles will influence the behavior of gas–solid flow critically. In order to deepen our insights into this important topic, in this work three typical cases: (1) double hot particles, (2) double cold particles, and (3) one hot and one cold particle, are investigated with the aid of direct numerical simulation of the Lattice Boltzmann method. A comprehensive comparison is carried out between them and some new interesting phenomena are observed. Our results show that thermal convection between particles will influence their behaviors significantly.